De danske husholdninger og stagnationspolitik - Madsen, Mogens Ove; Randrup Byrialsen, Mikael (Politik, 2017)
The Danish Economy, measured in terms of real GDP, has not yet recovered to the same level as 2007. The economy initially contracted and has since stagnated with little to no growth in real GDP. This article presents an alternative explanation for this stag-nation, which relies on an analysis inspired by the keynesian economist Josef Steindl. The contribution from Steindl has largely been ignored in the debate, despite its obvious potential. With the use of the theoretical foundation offered by Steindl, the stagnation of the Danish economy can be explained by a combination of the behavior of the house-hold, the investment behavior of firms and the public preoccupation with the fiscal budget. The political consequence of this focus on balancing the budget is also dis-cussed in detail towards the end of this article.